Analisa Backup Dan Replikasi Virtual Server Dengan Menggunakan Penjadwalan Koneksi Data Pada Disaster Recovery Center (DRC) - Pratama, Bayu Putra; Taryo, Taswanda; Hindansyah, Achmad (Universitas Pamulang, 2026)
Server backup and replication are critical components in ensuring operational continuity and disaster recovery within modern information systems. One of the main challenges faced is the unscheduled transfer of data between the Data Center (DC) and the Disaster Recovery Center (DRC), which can lead to the spread of viruses, malware, and ransomware into the DRC environment, thereby disrupting the recovery process. This study aims to analyze the effectiveness of data connection scheduling in the backup and replication of virtual servers at PT XYZ Finance. The research adopts a quantitative approach by measuring system performance before and after the implementation of scheduled replication. Quantitative parameters include replication time, volume of successfully transferred data, backup success rate, and recorded security incidents. Data were collected through direct system testing and analyzed using descriptive and comparative statistical methods. The results show that implementing a structured data connection schedule in the replication system significantly supports faster operational recovery and reduces the number of security incidents impacting the DRC. Based on these findings, scheduled data connections in server replication have proven to be quantitatively effective in improving system efficiency and security. Therefore, this approach is recommended as part of a data-driven disaster recovery strategy in enterprise IT environments.